From Google to Generative AI: Rethinking the role of library research guides - Lee, Yoo Young; Smith, Allison (Université d'Ottawa | University of Ottawa, 2026)
Since the introduction of ChatGPT in 2022, many studies have reported decreases in traffic to websites such as Google and Wikipedia, reflecting broader shifts in user information-seeking behaviour. To understand how these changes may affect academic libraries, we analyzed LibGuides traffic statistics and data from Google Analytics at our institution from their launch in 2015 through the present. Our study compares usage patterns before and after the emergence of ChatGPT, identifies where students accessed the guides from, and pinpoints which guides continue to be actively used in the era of generative AI. This investigation aims not only to trace the impact of tools like ChatGPT on library research guides but also to generate insights into how guides should be tailored and redesigned to support students’ evolving mental models and information-seeking behaviours. This presentation was delivered at 2026 OLA Super Conference in Toronto on January 30, 2026.
Keywords: LibGuides; Research guides; Generative AI; Informaion-seeking behaviours